2004
DOI: 10.1073/pnas.0305574101
|View full text |Cite
|
Sign up to set email alerts
|

WIN1, a transcriptional activator of epidermal wax accumulation inArabidopsis

Abstract: Epicuticular wax forms a layer of hydrophobic material on plant aerial organs, which constitutes a protective barrier between the plant and its environment. We report here the identification of WIN1, an Arabidopsis thaliana ethylene response factor-type transcription factor, which can activate wax deposition in overexpressing plants. We constitutively expressed WIN1 in transgenic Arabidopsis plants, and found that leaf epidermal wax accumulation was up to 4.5-fold higher in these plants than in control plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
369
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(385 citation statements)
references
References 50 publications
12
369
2
2
Order By: Relevance
“…This constitutive promoter has been used in mutant complementation experiments with a number of cuticular lipid synthesis genes. In particular, a number of genes involved in cuticular lipid biosynthesis and known to be differentially expressed in the epidermis (Suh et al, 2005) were highly induced by 35S-driven overexpression of the WIN1 transcription factor (Broun et al, 2004). Ectopic expression of GPAT5 was confirmed via reverse transcription-PCR transcript analysis of mRNA prepared from seven independent lines using leaves, an organ where GPAT5 is not expressed in wild type (data not shown).…”
Section: Accumulation Of Mags In Root Waxes Correlates With Gpat5 Expmentioning
confidence: 90%
See 1 more Smart Citation
“…This constitutive promoter has been used in mutant complementation experiments with a number of cuticular lipid synthesis genes. In particular, a number of genes involved in cuticular lipid biosynthesis and known to be differentially expressed in the epidermis (Suh et al, 2005) were highly induced by 35S-driven overexpression of the WIN1 transcription factor (Broun et al, 2004). Ectopic expression of GPAT5 was confirmed via reverse transcription-PCR transcript analysis of mRNA prepared from seven independent lines using leaves, an organ where GPAT5 is not expressed in wild type (data not shown).…”
Section: Accumulation Of Mags In Root Waxes Correlates With Gpat5 Expmentioning
confidence: 90%
“…In addition, overexpression of AP2 domaincontaining transcription factors (Aharoni et al, 2004;Broun et al, 2004;Zhang et al, 2005) has increased cuticular wax load, but no novel components were reported. This study shows that, with the appropriate biosynthetic gene, it is possible to produce novel cuticular wax components that are transported to the surface.…”
Section: Biotechnology Of Plant Cuticlesmentioning
confidence: 99%
“…Coordinated regulation of metabolic pathways controlling cuticle formation has been demonstrated for transcription factors of the SHINE/WAX-INDUCER family (Aharoni et al, 2004;Broun et al, 2004) and recently for MIXTA-like myeloblastosis (MYB) transcription factors (Oshima et al, 2013). Several of their downstream targets involved in cutin synthesis, modification, and assembly, as well as in cell wall formation and structure and in epidermal cell patterning (Shi et al, 2013), have been identified.…”
mentioning
confidence: 99%
“…This genetic switch involves multiple other TFs from diverse families such as the plantspecific APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ ERF) TFs that include major regulators of specific metabolic pathways. WIN1 and members of the SHINE-clade control biosynthesis of cuticular wax in Arabidopsis (Aharoni et al, 2004;Broun et al, 2004;Kannangara et al, 2007). ORA47 activates the expression of the jasmonate (JA) biosynthesis gene LOX3 (Pauwels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%